Fabrication and relining of dentures with permanent silicone soft liner: A novel way to increase retention in grossly resorbed ridge and minimize trauma of knife edge and severe undercuts ridges - Kunwarjeet Singh; Nidhi Gupta (Wolters Kluwer Medknow Publications, 2016)
The aim of this study is to suggest a technique to improve the retention of the prosthesis in grossly resorbed ridge and minimize the trauma of thin, atrophic knife edge ridge with severe undercuts. Significant numbers of patients seek treatment for edentulism throughout the world. In the current scenario, implant retained/supported prostheses have been considered a standard of care for rehabilitation of completely edentulous patients, but still this treatment modality is out of reach of many patients due to economic factor. In such patients, conventional removable complete dentures are considered for functional rehabilitation. However, in some of the patients with grossly resorbed ridges and knife edge ridges or ridges with severe undercuts, these prostheses have compromised retention and also continuously causes trauma to knife edge ridges and mucosa covering the undercuts during insertion and removal of the prosthesis thereby reducing the compliance of the patient. By incorporating, a layer of resilient permanent silicone soft liner on the tissue surface of a new or old denture is a novel way to reduce the trauma of thin and severe undercut ridges and also improve the retention of the prosthesis. This study described the successful functional rehabilitation of three completely edentulous patients with grossly resorbed, thin knife edge, and severe undercut mandibular ridges with permanent silicone soft liner. Permanent silicone soft liner act as a shock absorber, helps in equal dissipation of occlusal stresses, maintains an intimate contact with the underlying tissues and compressed during function thereby increasing retention and minimizing trauma by preventing a direct contact of hard denture base with compromised tissues.